Persepsi Guru Pembimbing terhadap Proses Pembelajaran Mahasiswa PPL UNY di SMK Kota Yogyakarta Tahun Ajaran 2012/2013 - Djoko Santoso; Niken Ayu Larasati; Ramlan Arief Fathony (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
This study describes perception of the supervisor teachers toward the skills of Yogyakarta State University students conducting Teaching Practicum at Vocational High Schools in Yogyakarta regency in the academic year of 2012/2013. This study was conducted using survey approach. The population were the teachers of the Industrial Technology program at Vocational High Schools in Yogyakarta regency. The results showed the perception toward the students’ skills in  high, average and low categories were 18.33%, 56.67% and 25% respectively. The reasons for the 25% of the low category were the students did not have sufficient experiences in teaching and did not completely master crucial components of the learning process, particularly in the opening stage